Analisis Model Pengelolaan Platform New Media Oleh Klub Sepakbola di Indonesia - Faridhian Anshari; Fathru Qalbie Septizar Akbar (Fakultas Ilmu Komunikasi Universitas Pancasila, 2019)
This study aims to determine what models are created from the management of the new media platform by football clubs in Indonesia. Furthermore, the results of this study will be compared with the new media management model conducted by European football clubs through the MOSC (Model for Online Sport Communication) approach. The benefit of this research is the creation of a model that can be used as a reference for other football clubs, in utilizing the new media platform. This study uses a qualitative approach in which data collection techniques will begin by using content analysis of all new media platforms for football clubs in Indonesia, which leads to the selection of ten clubs having the highest number of followers, where in the course of the journey there are only seven clubs namely Persib Persija, Arema, Persebaya Persela , PSIS, and PSS who are willing to be the main objects in this study. Furthermore, data collection techniques through in-depth interviews are also used by researchers to the media officer division to obtain research answers. This research produces findings in the form of the creation of three models in the management of new media platforms in Indonesian soccer clubs, namely: active interaction models, passive interactions, and non-interactions.